12q14 microduplication: a new clinical entity reciprocal to the microdeletion syndrome? - Sofia Dória; Daniela Alves; Maria João Pinho; Joel Pinto; Miguel Leão (BMC, 2020)
Abstract Background 12q14 microdeletion syndrome is characterized by low birth weight and failure to thrive, proportionate short stature and developmental delay. The opposite syndrome (microduplication) has not yet been characterized. Our main objective is the recognition of a new clinical entity - 12q14 microduplication syndrome. - as well as confirming the role of HMGA2 gene in growth regulation. Case presentation Array Comparative Genomic Hybridization (CGH), Karyotype, Fluorescence in situ Hybridization, Quantitative-PCR analysis and Whole exome sequencing (WES) were performed in a girl presenting overgrowth and obesity. Array CGH identified a 1.5 Mb 12q14.3 microduplication involving HMGA2, GRIP1, IRAK3, MSRB3 and TMBIM4 genes. Karyotype and FISH showed that duplication was a de novo insertion of 12q14.3 region on chromosome 9p resulting in an interstitial microduplication. Q-PCR confirmed the duplication only in the proband. WES revealed no pathogenic variants. Conclusions Phenotypic comparison with patients with 12q14 microdeletion syndrome showed a reciprocal presentation, suggesting a phenotypically recognizable 12q14 microduplication syndrome as well as confirming the role of HMGA2 gene in growth regulation. It is also indicative that other genes, such as IRAK3 and MSRB3 might have of role in weight gain and obesity.